NEED HELP ASAP WILL GIVE BRAINLIST IF CORRECT
![NEED HELP ASAP WILL GIVE BRAINLIST IF CORRECT class=](https://us-static.z-dn.net/files/d19/f981110b6fcc99ed0f885e6705f728e0.png)
Answer:
Multiplying both sides of Equation A by -3 gives 6.9x + 21 = -18
Step-by-step explanation:
-2.3x (-3) -7 (-3) = 6 ( -3)
6.9x+21 = -18
Multiply both sides of the equation by -3 is the right thing to do because you have make Equation A equal to Equation B and the only way to do that is by multiplying both sides of the equation by -3.
Hope this helps!!!